Association between Consumption of Coffee and the Prevalence of Periodontitis: The 2008–2010 Korea National Health and Nutrition Examination Survey - Han, Kyungdo (PLoS One, 2016)
BACKGROUND: This study was performed to assess the relationship between the consumption of coffee and periodontitis using nationally representative data. METHODS: The data from the Korea National Health and Nutrition Examination Survey were used; the analysis in this study was confined to a total of 16,730 respondents over 19 years old who had no missing values for the consumption of coffee or outcome variables. A community periodontal index greater than or equal to code 3 was defined as periodontal disease. RESULTS: Consumption of coffee was significantly higher in the individuals with periodontitis in males. The odds ratios of the percentage of individuals with periodontitis tended to increase with the consumption of coffee. Adjusted odds ratios and their 95% confidence intervals of the male participants were 1, 1.131(0.792–1.617), 1.161(0.857–1.573), 1.053(0.805–1.379), 1.299(1.007–1.676), and 1.458(1.141–1.862) for once per month or less, once per month<x≤3 times per week, three times per week<x≤6 times per week, once per day, twice per day, and three or more per day, respectively. CONCLUSIONS: Consumption of coffee may be considered an independent risk indicator of periodontal disease in Korean male adults, and we suggest that the periodontal health of male may benefit from reduction of coffee consumption.